PEMANFAATAN RUANG GURU DAN TENAGA KEPENDIDIKAN (GTK) SEBAGAI SARANA ASESMEN DAN INOVASI UNTUK PENGUATAN PENDIDIKAN MULTIKULTURAL - Rahmat Jilanuari; M.Fayis Gumelar; Rahmat Ary Zulkarnain (EDUCATOR : Jurnal Inovasi Tenaga Pendidik dan Kependidikan, 2025)
ABSTRACT This study is motivated by the importance of utilizing digital technology to improve the quality of learning and strengthen multicultural education, which has not yet been optimally implemented in many educational settings. The focus of this study is to examine the use of the Teacher and Education Personnel Platform (GTK) as a tool for assessment and innovation in strengthening multicultural education. This research employs a qualitative approach using a library research method, involving stages of identification, selection, classification, and content analysis of relevant scientific literature published within the last five years. The findings indicate that the use of digital platforms in education enhances the effectiveness of assessment through systems that are more flexible, efficient, and data-driven. In addition, digital learning innovation has been shown to increase students’ motivation, engagement, and access to learning, particularly in areas with limited resources. The integration of multicultural values in learning also contributes positively to character building, tolerance, and students’ awareness of diversity. However, several challenges remain, particularly related to teachers’ digital competencies and the integration of multicultural values in assessment practices. The study concludes that the utilization of the GTK platform has integrative potential in linking digital assessment, learning innovation, and multicultural Education, Thereby Creating An Adaptive, Inclusive, And Sustainable Learning System. ABSTRAK Penelitian ini dilatarbelakangi oleh pentingnya pemanfaatan teknologi digital dalam meningkatkan kualitas pembelajaran serta penguatan pendidikan multikultural yang belum optimal diimplementasikan di berbagai satuan pendidikan. Fokus penelitian ini adalah mengkaji pemanfaatan Ruang Guru dan Tenaga Kependidikan (GTK) sebagai sarana asesmen dan inovasi dalam memperkuat pendidikan multikultural. Penelitian menggunakan pendekatan kualitatif dengan metode studi pustaka (library research), melalui tahapan identifikasi, seleksi, klasifikasi, dan analisis isi terhadap literatur ilmiah yang relevan dalam lima tahun terakhir. Hasil penelitian menunjukkan bahwa pemanfaatan platform digital dalam pendidikan mampu meningkatkan efektivitas asesmen melalui sistem yang lebih fleksibel, efisien, dan berbasis data. Selain itu, inovasi pembelajaran digital terbukti dapat meningkatkan motivasi, keterlibatan, serta akses belajar peserta didik, termasuk di wilayah dengan keterbatasan sumber daya. Integrasi nilai-nilai multikultural dalam pembelajaran juga memberikan dampak positif terhadap pembentukan karakter, sikap toleransi, dan kesadaran kebhinekaan peserta didik. Namun demikian, masih terdapat kendala dalam implementasi, terutama terkait kompetensi digital guru dan integrasi nilai multikultural dalam asesmen pembelajaran. Simpulan penelitian ini menunjukkan bahwa pemanfaatan Ruang GTK sebagai platform digital memiliki potensi integratif dalam menghubungkan asesmen, inovasi pembelajaran, dan pendidikan multikultural, sehingga mampu menciptakan sistem pembelajaran yang adaptif, inklusif, dan berkelanjutan.